Analisis Efekktivitas Proses Stuffing dalam Mendukung Kelancaran Ekspor Produk Furniture di CV. More Than Teak International Jepara - Salsabila, Zahra; Erliyana, Sulida (Majalah Ilmiah Gema Maritim, 2025)
This research employs a qualitative descriptive method with a case study approach. Data was collected through observations, interviews with relevant parties, and an analysis of documentation related to the stuffing process within the company. The findings reveal that the effectiveness of stuffing is influenced by several key factors, including workforce readiness, adherence to standard packing procedures, and the availability of adequate stuffing facilities. Some of the challenges identified in the process include delays due to a lack of coordination, suboptimal container loading methods, and the risk of product damage during shipment. To enhance stuffing efficiency, the company is advised to conduct regular workforce training, optimize packing techniques, and improve coordination with logistics partners. By implementing these strategies, CV. More Than Teak International Jepara is expected to improve export efficiency and maintain its competitive advantage in the global market.